Dampak Keterlibatan Influencer, Konten Kreatif dan Strategi Kreatif terhadap Niat Membeli : Peran Mediasi Kesadaran Merek (Studi Kasus Citraland Puncak Tidar Malang) - Kencana, Wilissanti Giwang; Krisprimandoyo, D. Agung (IPM2KPE, 2024)
This study aims to explore the influence of digital marketing, especially the use of Influencers, Creative Content, and Creative Strategy, on purchase intention in a competitive property market, with a focus on the role of Brand Awareness. Using quantitative methods, this study involved 52 customers of CitraLand Puncak Tidar Malang who had made purchases, and data analysis was carried out using PLS-SEM using SmartPLS 3.3.3. The results showed that although Influencers, Creative Content, and Creative Strategy had a positive relationship with Brand Awareness, the relationship was not significant. On the other hand, Brand Awareness had a positive relationship with Purchase Intention but was also not significant. Creative Content showed a positive relationship with Purchase Intention, but was not significant. On the other hand, the Use of Influencers and Creative Strategy showed a significant positive relationship with Purchase Intention. In conclusion, the variables studied are relevant in explaining data patterns in the property market, although some relationships are not significant. Keywords: Influencers, Creative Content, Brand Awareness, Purchase Intention, Creative Strategy